Justiça ambiental para as futuras gerações - Gomes, Keit Diogo (2017)
ABSTRACT: The current research analyzes environmental justice with a focus on future generations. Environment protection for future generations is a justifiable mean to ensure environmental protection, under the risk of environmental resources depletion and unfeasibility of their balanced use for the generations to come. The study is constructed in three sections. The first chapter is intended to present the theory of environmental justice, explaining the concept of justice and environmental injustice, indicating the historical context and social cases that led the theory to emerge, and highlighting the main recipients of environmental justice. On the second part, the text is intended to identify who the future generations are, and presents the intergenerational equity theory and the principles formulated by Edith B. Weiss, as well as other specialized scholars. The following chapter indicates the main legal instruments that oversees intergenerational environmental protection and analyzes the feasibility of future generations being seen as rights holders. The third section is dedicated to discuss alternatives that can be implemented on the search for intergenerational environmental justice, asserting the feasibility of local and global environmental governance, as well as a paradigm shift consistent with the prevalence of an environmental ethic, and also on the adoption of international mechanisms such as the establishment of an international environmental Tribunal and the use of the DSD - Dispute System Design - to mediate environmental conflicts. The research was primarily bibliographical and documental, using qualitative and deductive approach on data analysis.